Perjuangan Perempuan Kota Tomohon Pada Kontestasi Politik Lokal - Sangputri Sidik; Awaluddin Hasrin; Siti Fathimah; Hamsah Hamsah; Sanita Carolina Sasea (Universitas Lambung Mangkurat, 2023)
This study discusses the form of political participation of women in Tomohon City. The presence of women in the Indonesian political stage is an important discourse on the progress of democracy in Indonesia. However, there are still many obstacles among women to appear in political contestation, especially in political contestation. This research shows that the trend of political participation among women in Tomohon City continues to increase. This can be seen from the presence of female mayoral candidates who ran in the contestation of the 2019 Tomohon City Elections, namely Jilly Gabriel Eman paired with Virgie Baker. In the executive area, there are at least 40% of women who position as members of the Tomohon City Parliament. Meanwhile, in the aspect of election organizers, there are women representatives in the KPU and BAWASLU of Tomohon City. This condition does not necessarily mean that the involvement of women in the world of politics goes smoothly, but there are still obstacles that must be faced by women in participating in the world of politics in Tomohon City This research also aims to always revive gender discussions in social life. Gender mainstreaming is one of the agendas that must continue to be implemented in various sectors and lines of social life, especially in the academic environment.